PENERAPAN TEKNOLOGI DALAM PEMBELAJARAN MATEMATIKA SD - Nurhaswinda; Afifa Raisya Sahira; Neza Zulfazni; Mahtur Rahma; Zahra Salsabilla (STKIP Subang, 2026)
Education and technology are inseparable, as technology plays a crucial role in transforming the way we learn and teach. Without technology, education remains trapped in outdated, ineffective methods and unable to utilize various innovations that can improve the quality of the learning process. The purpose of this paper is to examine the application of technology in elementary school mathematics learning. This paper employs a library research approach. Information was obtained from academic papers published in journals and articles focused on the topic. Mathematics, often viewed as a complex and imprecise subject, can become more engaging and simpler to understand with the support of technology. For this reason, the use of technology in mathematics teaching is a crucial step in improving the quality of the teaching and learning process at the elementary level. Implementation of technology in elementary school mathematics teaching can be achieved through the use of MUZAX learning media, Snakes and Ladders games, learning tools for multiplication and division, and various forms of learning media such as comics and multimedia.